Common Values in Social Studies Textbooks for Basic Education (Third Cycle /Grade Seven as a Sample) - Awat Karim Mustafa, Asst. Lect (lark, 2025)
The aim of the research is to identify and determine the prevailing values in the Social Studies textbook for the basic stage/seventh grade according to Ralph White's content analysis criteria. To achieve the research objectives, the researcher used the descriptive analytical method, and the research tool consisted of using Ralph White's criteria. The research population consists of all basic stage teachers in the Sulaymaniyah Education Directorate, and the tool was applied to the research sample represented in the seventh-grade Social Studies textbook. The research found that out of the total (180) pages that make up the book, (97) pages are dedicated to topics and images, equivalent to (53.89%) of the book, and (83) pages are dedicated to other topics, equivalent to (46.11%).
Keywords: school textbooks, social subjects, basic stage